Exergy analysis and performance optimization of Kalina cycle system 11 (KCS-11) for low grade waste heat recovery. (February 2019) - Long, Rui; Kuang, Zhengfei; Li, Baode; Liu, Zhichun; Liu, Wei
Abstract: The internal and external exergy efficiencies are adopted to analyze the impacts of the evaporating pressure and ammonia fraction of the ammonia-water mixture on the performance of the Kalina system 11 (KCS-11) to harvest low grade waste heat. Results reveal that there exist optimal evaporating pressures leading to the maximum internal and external exergy efficiencies, respectively, while the internal exergy efficiency increases monotonously with increasing ammonia fractions, and the impacts of the ammonia fractions on the external exergy efficiency exhibit different behaviors, which depends on the evaporating pressure. However, the overall exergy efficiency has a maximum value for a given heat source inlet temperature. By taking exergy efficiency as an objective function, an optimal analysis is conducted to illuminate the impact of parameters on internal and external exergy efficiencies.